Cowpea seed coats and their extracts : phenolic composition and use as antioxidants in sunflower oil - Duodu, Kwaku Gyebi (University of Pretoria, 2013)
Dissertation (MInst.Agrar (Food Production and Processing))--University of Pretoria, 2007.